1993
DOI: 10.1161/01.hyp.21.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes synthesize angiotensinogen.

Abstract: To determine whether leukocytes express the angiotensinogen gene, we subjected circulating rat leukocytes and murine bone marrow cells to Northern blot analysis and hybridization with homologous angiotensinogen complementary DNA. Angiotensinogen messenger RNA sequences were detected in circulating adult rat leukocytes, in murine-irradiated and nonirradiated bone marrow stromal cells, and in an adherent stromal cell line (preadipocyte). Western blot analysis of rat leukocyte homogenate showed that rat leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 36 publications
0
65
0
2
Order By: Relevance
“…[20][21][22] We hypothesized this mobile RAS might be responsible for the effect of captopril on neutrophil hypersegmentation. To identify RAS components in human neutrophils, the presence of ACE in human neutrophils was examined by reverse transcription polymerase chain reaction (RT-PCR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] We hypothesized this mobile RAS might be responsible for the effect of captopril on neutrophil hypersegmentation. To identify RAS components in human neutrophils, the presence of ACE in human neutrophils was examined by reverse transcription polymerase chain reaction (RT-PCR).…”
Section: Resultsmentioning
confidence: 99%
“…20 Alveolar macrophages express ACE and produce Ang II in human atherosclerotic plaques. 21 Circulating rat leukocytes are also reported to secrete angiotensinogen, 22 and human mononuclear leukocytes possess functional components of RAS that can generate Ang II locally. 30,31 These studies suggest that a mobile RAS present on leukocytes contributes to circulating Ang II levels.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II can directly activate immune cells and regulate their functions inducing chemotaxis, proliferation, differentiation and phagocytosis (Mattana et al, 1995;Suzuki et al, 2002;Ruiz-Ortega and Ortiz, 2005). Immune cells express all the components of RAS and can produce angiotensinogen (Gomez et al, 1993;Okamura et al, 1999). RAS components have been identified in human ciliary body and aqueous humor (Cullinane et al, 2002) and involvement of RAS in ocular inflammation has been suggested by Nagai et al (Nagai et al, 2005), who proved the suppression of endotoxin-induced uveitis (EIU) by an angiotensin II type 1 receptor (AT1-R) inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an increasing body of evidence showing the involvement of the RAS in inflammatory diseases (2,3). Indeed, inflammatory cells have several components of the RAS (3,4), and components of the RAS are upregulated in synovium samples obtained from rheumatoid arthritis (RA) patients (5,6). Moreover, several studies have now shown the ability of Ang II to induce leukocyte migration, chemokine production, and activation of the transcription factor NF-kB (7,8).…”
mentioning
confidence: 99%